Blood meal as nitrogen source and its effect on disease severity on sweet corn - de Jesus Egues Martins, Karina; Klem Miliati, Camila; Viegas Neto, Antonio Luiz; Maria Maraschi da Silva Piletti, Lígia; Pelloso de Carvalho, Rafael; Roberto Rigotte, Márcio (Revista Agrogeoambiental, 2021)
A blood meal is a by-product of the meat processing industry and can be used as nitrogen fertilizer due to its minimum content of 10 % Nitrogen. The objective of this work was to evaluate the effect of doses of blood meal, such as nitrogen fertilizer in topdressing, on the production components and the severity of diseases in sweet corn. The experiment was developed at the Federal Institute of Education, Science and Technology of Mato Grosso do Sul (IFMS), Ponta Porã campus, in a Quartzarenic Neosol. The experimental design used was randomized blocks with five treatments of blood meal doses of (0 kg ha-1; 48 kg ha-1; 96 kg ha-1; 120 kg ha-1 and 144 kg ha-1) and one treatment using urea for topdressing fertilization with 120 kg ha -1 of N. The experiment analyzed the severity of white spot on the tasseling and milk grain stages and also the production components: plant height, insertion height of the first ear, stalk diameter, length of the unhusked commercial ears, diameter of unhusked commercial ears, number of grain row, weight of husked commercial ears, weight of unhusked commercial ears and productivity in kg ha-1. The use of blood meal was as efficient as the use of urea as a nitrogen fertilizer for doses starting from 48 kg ha-1, the maximum productivity was obtained when the dose of 112 kg ha-1 of N blood meal was used. The severity of the white spot did not progress in treatments containing nitrogen fertilization in topdressing.